A brief procedure to fabricate soils from coal mine wastes based on mineral processing, agricultural, and environmental concepts. (15th May 2015) - Firpo, Beatriz Alicia; Amaral Filho, Juarez Ramos do; Schneider, Ivo André Homrich
Highlights: It was developed a procedure to fabricate topsoils from coal mine wastes. Steps: gravity separation, comminution/classification, amendments, and plant growth. A validation was conducted by Sorghum bicolor growth. Fabricated soils are potential substitutes for natural soils in reclamation projects. Abstract: The objective of this work was to propose a procedure to fabricate topsoils from coal mine wastes. It comprises the following steps: gravity processing, comminution and classification, amendments (pH adjustment and addition of active organic matter), soil analysis, and plant growth (macro- and micro-nutrients and metals concentration). Validation was conducted with a coal mine waste amended with steel slag and sewage sludge, which was successfully applied for Sorghum bicolor growth.